An Application of Grey Wolf Optimizer for Solving Combined Economic Emission Dispatch Problems - Hong, Mee Song; M. H., Sulaiman; Mohd Rusllim, Mohamed (Praise Worthy Prize, 2014)
Grey Wolf Optimizer (GWO) is a newly proposed algorithm that developed based on inspiration of grey wolves (Canis Lupus). This GWO algorithm mimics the nature of grey wolves in leadership hierarchy and hunting mechanism. This paper is in the purpose of introducing GWO to solve combined economic emission dispatch problem (CEED) in power system. CEED actually is a bi-objective problem where the objective of economic dispatch (ED) and emission dispatch (EMD) are combined into a single function by using price penalty factor. Hence, CEED is used to minimize total generation cost by minimized fuel cost and emission at the same time determines the optimum power generation. The proposed algorithm will be implemented in two different systems which are 6 and 11-generating unit test systems with different constraints on various power load demands. The results were compared with the optimization techniques reported in recent literature in order to observe the effectiveness of GWO.